Prostatic Inflammation Induces Fibrosis in a Mouse Model of Chronic Bacterial Infection - Wong, Letitia (Public Library of Science, 2014)
Inflammation of the prostate is strongly correlated with development of lower urinary tract symptoms and several studies have implicated prostatic fibrosis in the pathogenesis of bladder outlet obstruction. It has been postulated that inflammation induces prostatic fibrosis but this relationship has never been tested. Here, we characterized the fibrotic response to inflammation in a mouse model of chronic bacterial-induced prostatic inflammation. Transurethral instillation of the uropathogenic E. coli into C3H/HeOuJ male mice induced persistent prostatic inflammation followed by a significant increase in collagen deposition and hydroxyproline content. This fibrotic response to inflammation was accompanied with an increase in collagen synthesis determined by the incorporation of (3)H-hydroxyproline and mRNA expression of several collagen remodeling-associated genes, including Col1a1, Col1a2, Col3a1, Mmp2, Mmp9, and Lox. Correlation analysis revealed a positive correlation of inflammation severity with collagen deposition and immunohistochemical staining revealed that CD45+VIM+ fibrocytes were abundant in inflamed prostates at the time point coinciding with increased collagen synthesis. Furthermore, flow cytometric analysis demonstrated an increased percentage of these CD45+VIM+ fibrocytes among collagen type I expressing cells. These data show–for the first time–that chronic prostatic inflammation induces collagen deposition and implicates fibrocytes in the fibrotic process.